(untitled) (Eurasian Research Bulletin, 2025)
Bronchial asthma is a chronic persistent inflammation and pathological process characterized by airway obstruction, including the bronchi, manifested by episodes of suffocation or asthmatic conditions. In the 21st century, bronchial asthma remains a significant focus in global scientific research. First, this disease is widespread, and this trend is expected to continue for at least the next ten years. Second, bronchial asthma has become not only a medical issue but also an important socio-economic problem for states. Third, epidemiological studies play a crucial role in addressing issues related to bronchial asthma, but, despite this, such research has significantly decreased in the CIS countries.